Essential Blepharospasm - Jordan, D.R. (Canadian Journal of Optometry, 2026)
Essential blepharospasm is an idiopathic disorder characterized by progressive involunrary spasms of the orbicularis oculi and upper facial muscles (the corrugator and procerus). The resulting spasm is bilateral, sponraneous, intermittent and involuntary. While blepharospasm may be an isolated condition, many patients also have, or will develop, contraction of other facial, oromandibular, or cervical muscles. This paper will describe the clinical features of blepharospasm, the differenrial diagnosis, and current treatment modalities.